Implementation of Criminal Law on Tax Evasion in the Policy of Harmonizing Tax Regulations (Qawanin Jurnal Ilmu Hukum, 2025)
This research discusses the application of criminal law on tax evasion in the context of tax regulation harmonization policy in Indonesia. The main focus of this research is to analyze two things, namely: first, legal arrangements related to alleged tax evasion based on positive law in Indonesia, and second, the application of criminal law to alleged tax evasion as stipulated in Law Number 7 of 2021 concerning Harmonization of Tax Regulations. The research method used in this research is normative legal research (doctrinal), using the statue approach, analytical approach, and conceptual approach. The research data presented is sourced from primary, secondary, and tertiary legal materials. The study results show that: Legal arrangements for alleged tax evasion in Indonesia are regulated through the Harmonization of Tax Regulations legislation which provides the legal basis for prosecuting the crime, including its elements. However, in Decision Number: 75/Pid.Sus-Tpk//2023/Pn.Jkt.Pst, the application of these provisions was not prioritized. The Public Prosecutor only focused on corruption and money laundering crimes, where tax evasion became a predicate crime for money laundering. Abstrak:Penelitian ini membahas penerapan hukum pidana atas penggelapan pajak dalam konteks kebijakan harmonisasi peraturan perpajakan di Indonesia. Fokus utama penelitian ini adalah untuk menganalisis dua hal, yaitu: pertama, pengaturan hukum terkait dugaan penggelapan pajak berdasarkan hukum positif di Indonesia, dan kedua, penerapan hukum pidana terhadap dugaan penggelapan pajak sebagaimana diatur dalam Undang-Undang Nomor 7 Tahun 2021 tentang Harmonisasi Peraturan Perpajakan. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian hukum normatif (doktrinal), dengan menggunakan metode pendekatan statue approach, analytical approach, dan conceptual approach. Data penelitian yang disajikan bersumber dari bahan hukum primer, sekunder, dan tersier. Hasil kajian menunjukan bahwa: Pengaturan hukum atas dugaan penggelapan pajak di Indonesia diatur melalui perundang-undangan Harmonisasi Peraturan Perpajakan yang memberikan dasar hukum penindakan tindak pidana tersebut, termasuk unsur-unsurnya. Namun, dalam Putusan Nomor: 75/Pid.Sus-Tpk//2023/Pn.Jkt.Pst, penerapan ketentuan tersebut tidak diutamakan. Jaksa Penuntut Umum hanya berfokus pada tindak pidana korupsi dan pencucian uang, di mana penggelapan pajak menjadi predicate crime bagi tindak pidana pencucian uang.